Potential use of cameron highlands reservoir sediment in compressed bricks - Chua H.-Q.; Ean L.-W.; Mohammed B.S.; Malek M.A.; Wong L.S.; Tang C.-W.; Lee Z.-K.; Lim A.-F.; See Y.-Y.; Ooi J.-L.; Hashim M.; Yong U.; et al. (Trans Tech Publications Ltd, 2023)
The objective of this research is to investigate the potential use of Cameron Highland reservoir sediment in compressed brick production. The sediments can be classified as well-graded clayey sandy SILT and well-graded gravely SAND whereby the grain size is comparable to the grain size of sand and silt. The sediment was used as a 100 % replacement for the soils content in conventional soil cement bricks. Besides that, sodium bentonite, mica, fly ash and bottom ash are used as pozzolan to partially replace the cement in the sediment cement bricks. This paper presents the compressive strength of sediment cement brick incorporating sodium bentonite, mica, bottom ash and fly ash as partial replacement of cement. The total replacement of soils by Cameron Highland reservoir sediment (Mix 2) shows significant increase in compressive strength of the bricks compare to the conventional soil cement bricks (Mix 1), while partial replacement of 10 % pozzolan results in optimum strength. On the other hand, 10 % of bottom ash and 10 % of fly ash (Mix 13) as partial replacement of cement achieved the highest compressive strength. This implies that sodium bentonite, mica, fly ash and bottom ash can be used as pozzolan to partial replace the cement. Copyright © 2014 Trans Tech Publications Ltd, Switzerland.